POTRFOLIO MANAGEMENT WITH TIME SERIES ANALYSIS METHODS - І. С. Лазаренко; Є. О. Крикун (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
The purpose of this research is to review and summarize the theoretical and methodological foundations of portfolio theory, methodological provisions for modeling an optimal portfolio using time series. To achieve the goal, the article used the modern portfolio theory of Harry Markowitz (MPT), which emphasizes the importance of diversification and quantitative assessment of risks and returns. The study also explore the adaptation of ARIMA and GARCH models for forecasting risk matrices, offering a nuanced approach to forecasting and utilizing market fluctuations to achieve optimal portfolio performance. The results of the study not only confirm the relevance of fundamental theories of portfolio management in the current environment, but also expand the toolkit for investors through the practical application of advanced time series analysis methodologies. The practical significance of the study is to provide investors with reliable strategies that will help them navigate and benefit from market dynamics, thereby maximizing investment results in the face of uncertainty inherent in financial markets.